Financial development, financial liberalization and social capital. Issue 11 (3rd March 2018) - Elkhuizen, Luuk; Hermes, Niels; Jacobs, Jan; Meesters, Aljar
ABSTRACT: The relationship between financial liberalization policies and financial development is controversial. The impact of these policies differs greatly across countries. In the literature, the quality of formal institutions has been identified as an important source of this heterogeneity, as countries with a weak institutional environment generally fail to benefit from financial liberalization. Using panel data covering 82 countries for the period 1973–2008, we find evidence that social capital may substitute for formal institutions as a prerequisite for effective financial liberalization policies. In particular, we find that during the post Washington-consensus period countries with a high prevailing level of social capital can ensure that financial liberalization positively influences financial development, despite the poor quality of their formal institutions.